Living Qur’an in the Massoppo’i Wai Tradition: Negotiating Orthodoxy and Local Belief in Polewali Mandar - Sulkifli Sulkifli; Makmur Makmur; Lathifahcahyani; Moh. Mauluddin; Yusriah Yusriah (Jurnal Studi Agama dan Masyarakat, 2026)
This study examines the negotiation between religious orthodoxy and local belief within the Massoppo’i Wai tradition of the Mandar community in Polewali Mandar Regency, West Sulawesi, Indonesia. Massoppo’i Wai is a rain-diversion ritual performed prior to weddings and communal ceremonies, which has undergone gradual Islamization while retaining pre-Islamic cosmological elements. Employing qualitative fieldwork within the Living Qur’an framework, this study investigates how Qur’anic verses are received, appropriated, and functionally deployed at the intersection of Islamic normativity and indigenous belief systems. The findings reveal significant diversity in ritual practice: some practitioners incorporate Qur’anic recitation as a central element, while others perform the ritual without direct Qur’anic reference, reflecting varying degrees of Islamic internalization. From an exegetical reception standpoint, the verses are interpreted as acts of devotion, petitions for divine protection, or reverence toward ancestral spirits; from a functional reception perspective, they serve as vehicles of collective prayer and communal hope. This study argues that Massoppo’i Wai constitutes a living site of Qur’anic reception where Islamic textual authority and Mandar cosmology are continuously negotiated, producing a hybrid religious practice that resists categorization as either orthodox Islam or mere syncretism. Empirically, this study offers the first systematic ethnographic account of Qur’anic reception in this tradition; theoretically, it reconceptualizes orthodoxy not as a fixed standard imposed upon local practice, but as a contested horizon within which ritual actors exercise interpretive agency.